2021
DOI: 10.1007/s10903-021-01189-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hospitalization Among Patients with COVID-19 at a Community Ambulatory Clinic in Massachusetts During the Initial Pandemic Surge

Abstract: Among patients with COVID-19 evaluated in outpatient settings, factors associated with hospitalization remain poorly understood. Multivariable regressions were used to assess sociodemographic and clinical factors associated with increased odds of hospitalization among patients with confirmed COVID-19 between March 18, 2020 through April 25, 2020 at a community-based outpatient clinic in Massachusetts. Older age, BMI ≥ 25, self-reported dizziness/lightheadedness, temperature ≥ 99.5°F, tachycardia, and oxygen sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…These findings clarify the results of studies performed in Minnesota, California, and Massachusetts [ 5 , 6 , 12 ]. The California and Minnesota studies used death certificate data and found higher mortality from COVID-19 in all foreign-born groups but particularly Hispanic men.…”
Section: Discussionsupporting
confidence: 85%
“…These findings clarify the results of studies performed in Minnesota, California, and Massachusetts [ 5 , 6 , 12 ]. The California and Minnesota studies used death certificate data and found higher mortality from COVID-19 in all foreign-born groups but particularly Hispanic men.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings extend the literature on the impact of social and structural determinants on SARS-CoV-2 infection [ 26 , 27 ], hospitalization [ 28 ], and mortality [ 29 , 30 ]. Racial and ethnic disparities in SARS-CoV-2 risk are well documented in COVID-19, suggesting that Black and Hispanic individuals are at greater risk for infection and poor outcomes [ 27 , 29 , 31 ].…”
Section: Discussionsupporting
confidence: 85%
“…19 Certain ethnicities, such as African American and Hispanic American have also emerged as risk factors for death and severe disease in the US, presumably in connection with social determinants of health. 2,20,21 Migrants in high income countries are also at higher risk of exposure and infection, but outcome data are lacking. 22 Despite the extensive literature on risk factors, it stands to reason that clinical symptoms (such as dyspnoea and altered mentation) and oxygen saturation measurements have remained as the main indicators of deterioration and criteria for hospital admission in national guidelines.…”
Section: Introductionmentioning
confidence: 99%